Surface electromyography based muscle fatigue detection using high-resolution time-frequency methods and machine learning algorithms. (February 2018) - Karthick, P.A.; Ghosh, Diptasree Maitra; Ramakrishnan, S.
Highlights: sEMG based muscle fatigue detection is widely preferred and these signals exhibit higher degree of nonstationarity. B-distribution, extended modified B-distribution (EMBD) and S-transform based TFDs are proposed to address this property. Twelve features and five classifiers are employed along with two feature selection techniques. Appropriate time-frequency based features are determined to distinguish muscle nonfatigue and fatigue conditions. An accuracy of 91%% is achieved by using genetic algorithm selected features and SVM, for EMBD time-frequency method. Abstract: Background and objective: Surface electromyography (sEMG) based muscle fatigue research is widely preferred in sports science and occupational/rehabilitation studies due to its noninvasiveness. However, these signals are complex, multicomponent and highly nonstationary with large inter-subject variations, particularly during dynamic contractions. Hence, time-frequency based machine learning methodologies can improve the design of automated system for these signals. Methods: In this work, the analysis based on high-resolution time-frequency methods, namely, Stockwell transform (S-transform), B-distribution (BD) and extended modified B-distribution (EMBD) are proposed to differentiate the dynamic muscle nonfatigue and fatigue conditions. The nonfatigue and fatigue segments of sEMG signals recorded from the biceps brachii of 52 healthy volunteers are preprocessed and subjected to S-transform, BD and EMBD. Twelve features are extracted from each method and prominent features are selected using genetic algorithm (GA) and binary particle swarm optimization (BPSO). Five machine learning algorithms, namely, naïve Bayes, support vector machine (SVM) of polynomial and radial basis kernel, random forest and rotation forests are used for the classification. Results: The results show that all the proposed time-frequency distributions (TFDs) are able to show the nonstationary variations of sEMG signals. Most of the features exhibit statistically significant difference in the muscle fatigue and nonfatigue conditions. The maximum number of features (66%) is reduced by GA and BPSO for EMBD and BD-TFD respectively. The combination of EMBD- polynomial kernel based SVM is found to be most accurate (91% accuracy) in classifying the conditions with the features selected using GA. Conclusions: The proposed methods are found to be capable of handling the nonstationary and multicomponent variations of sEMG signals recorded in dynamic fatiguing contractions. Particularly, the combination of EMBD- polynomial kernel based SVM could be used to detect the dynamic muscle fatigue conditions.